CLINICAL PROFILES OF VITILIGO WITH NARROWBAND UVB AND TOPICAL CORTICOSTEROID THERAPY AT DR. SOETOMO HOSPITAL - Sarah Fauzia; Rahmadewi Rahmadewi; Dyah Fauziah (Jurnal Berkala Epidemiologi, 2020)
Background: Vitiligo is a depigmenting disorder that causes a loss of melanocytes in the epidermis. Treatment preferences are based on the characteristics of the vitiligo lesions. Purpose: This study evaluates the clinical profiles of vitiligo treated with narrowband UVB (NB-UVB) radiation and topical corticosteroid therapy in Dr. Soetomo Hospital in 2017. Methods: This study is a retrospective study that uses data from the medical records of vitiligo patients who were treated with NB-UVB radiation and topical corticosteroids in Dr. Soetomo Hospital in 2017. The dependent variable was vitiligo treated with NB-UVB radiation or topical corticosteroids, while the independent variables were disease onset, precipitating factor, duration, stability, amount, affected area, location, and type of vitiligo. Results: Thirty-seven patients (19 females) were included, four of whom had been treated with NB-UVB radiation and 33 with topical corticosteroids. In the NB-UVB radiation group, 75% had stable lesions, 50% had a single lesion, 50% had multiple lesions, 75% had an affected area <10cm2, 40% had lesions around their face, 40% had lesions on their extremities, and 75% had focal vitiligo. In the topical corticosteroids group, 75.76% had active lesions, 81.82% had multiple lesions, 81.82% had an affected area <10 cm2, 28.21% had lesions around their upper extremities, 28.21% had lesions around their lower extremities, and 45.45% had segmental vitiligo. Conclusion: Treatment preference in Dr. Soetomo Hospital 2017 was indicated by the patients’ clinical profiles.